Eicosapentaenoic Acid for Cardiovascular Events Reduction- Systematic Review and Network Meta-Analysis of Randomized Controlled Trials. Issue 5 (November 2022) - Yokoyama, Yujiro; Kuno, Toshiki; Morita, Sae X.; Slipczuk, Leandro; Takagi, Hisato; Briasoulis, Alexandros; Latib, Azeem; Bangalore, Sripal; Heffron, Sean P.
Abstract: Background: Randomized clinical trials (RCTs) investigating the impact of omega-3-fatty acid supplementation on cardiovascular events have largely shown no benefit. However, there is debate about the benign nature of the placebo in these trials. We aimed to conduct a network meta-analysis of RCTs to compare the outcomes of omega-3 fatty acid supplementation to various placebo oils. Methods: MEDLINE and EMBASE were searched through May, 2021 to identify RCTs investigating cardiovascular outcomes with omega-3-fatty acid formulations [eicosapentaenoic acid (EPA), decosahexanoic acid (DHA), or the combination] versus placebo or standard of care controls. Results: Our analysis included 17 RCTs that enrolled a total of 141, 009 patients randomized to EPA (n=13, 655), EPA+DHA (n=56, 908), mineral oil placebo (n=5, 338), corn oil placebo (n =8, 876), olive oil placebo (n=41, 009), and controls (no placebo oil; n=15, 223). Rates of cardiovascular death [hazard ratio (HR) (95% confidence interval, CI) =0.80 (0.65-0.98); p =0.033], myocardial infarction [HR (95% CI) =0.73 (0.55-0.97); p =0.029] and stroke [HR (95% CI) =0.74 (0.58-0.94); p =0.014] were significantly lower in those receiving EPA compared to those receiving mineral oil, but were not different from rates in those receiving other oils or controls. Rates of coronary revascularization were significantly lower in those receiving EPA than in those receiving either EPA+DHA, mineral oil, corn oil, or olive oil placebo, but not controls. All-cause death was similar among all groups, but combined EPA+DHA was associated with reduced risk of cardiovascular death compared to controls [HR (95%CI): 0.83 (0.71-0.98)]. Conclusions: Our analyses demonstrate that although EPA supplementation lowers risk of coronary revascularization more than other oils, there may not be a benefit relative to standard of care. Further, EPA reduces the risk of cardiovascular events only in comparison to mineral oil and not when compared with other placebo oils or controls. In contrast, combined EPA+DHA was associated with reduced risk of cardiovascular death compared to controls. Graphical Abstract: Left: A network plot of eligible comparisons among groups. The width of connecting lines between the second conduit strategies reflects the number of studies available for each comparison. Right: Forest plots of EPA or EPA+DHA versus controls for all outcomes. DHA, docosahexaenoic acid; EPA, eicosapentaenoic acid. Unlabelled Image Highlights: We compared the outcomes of omega-3 fatty acid [eicosapentaenoic acid (EPA) or decosahexanoic acid (DHA)] to various placebo oils. Major adverse cardiac events were lower with EPA compared to mineral oil, but not different from other oils. Coronary revascularization was lower in EPA than EPA+DHA, oils, but not controls.